2009
DOI: 10.1111/j.1600-0501.2008.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind randomized controlled trial study on post‐extraction immediately restored implants using the switching platform concept: soft tissue response. Preliminary report

Abstract: This study suggests that, in a limited time period of 2 years, immediately placed implants with subsequent platform switching can provide peri-implant tissue stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(163 citation statements)
references
References 25 publications
13
147
0
3
Order By: Relevance
“…In the present study, retraction at the 12-month follow-up for Group A immediate implants was 17.6% (0.43±0.56mm) compared to 8.7% (0.15±0.26mm) for Group B implants placed at healed sites. These results coincide with the findings obtained in other studies (21,22), who obtained values ranging between 0.41 and 0.55mm for immediately placed implants.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, retraction at the 12-month follow-up for Group A immediate implants was 17.6% (0.43±0.56mm) compared to 8.7% (0.15±0.26mm) for Group B implants placed at healed sites. These results coincide with the findings obtained in other studies (21,22), who obtained values ranging between 0.41 and 0.55mm for immediately placed implants.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, a similar study found no difference between platform switching and platform matching (on average from 7.71 to 7.51 –0.2mm- vs. 9 to 8.57 -0.4mm-) (26). …”
Section: Resultsmentioning
confidence: 98%
“…Platform expansion in post-extraction situations makes it possible to minimize the gap between the recently extracted tooth bed and the implant, acting as a physical barrier against the penetration of bacteria in the zone of contact between the bone and implant. This increase in diameter favors improved primary stability (15,(28)(29)(30)(31).…”
Section: E404mentioning
confidence: 99%